1997
DOI: 10.1136/bmj.314.7094.1584
|View full text |Cite
|
Sign up to set email alerts
|

Influence of cholesterol on survival after stroke: retrospective study

Abstract: Objective: To study the comparative importance of environment and genes in the development of islet cell autoimmunity associated with insulin dependent diabetes mellitus. Design: Population based study of diabetic twins. Setting: Danish population. Subjects: 18 monozygotic and 36 dizygotic twin pairs with one or both partners having insulin dependent diabetes. Main outcome measures: Presence of islet cell antibodies, insulin autoantibodies, and autoantibodies to glutamic acid decarboxylase (GAD65) in serum sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
63
2
4

Year Published

1999
1999
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(77 citation statements)
references
References 16 publications
8
63
2
4
Order By: Relevance
“…For example, the Lausanne Stroke Registry demonstrated that stroke patients with higher cholesterol levels had better outcomes after 1 month (Vauthey et al, 2000). In agreement with this, a retrospective study performed by Dyker et al (1997) found more patients dead or disabled after stroke with low cholesterol levels at stroke onset (Dyker et al, 1997). Taken together, there are many open questions regarding the relationship between cholesterol and stroke.…”
Section: Stroke and Cholesterol: The First Paradoxsupporting
confidence: 56%
“…For example, the Lausanne Stroke Registry demonstrated that stroke patients with higher cholesterol levels had better outcomes after 1 month (Vauthey et al, 2000). In agreement with this, a retrospective study performed by Dyker et al (1997) found more patients dead or disabled after stroke with low cholesterol levels at stroke onset (Dyker et al, 1997). Taken together, there are many open questions regarding the relationship between cholesterol and stroke.…”
Section: Stroke and Cholesterol: The First Paradoxsupporting
confidence: 56%
“…72 However, in the acute stroke setting, several studies have shown the opposite; that is, low cholesterol levels are associated with short-term mortality or worse functional outcome in patients with ischemic stroke, particularly in those who are older. [73][74][75] Several pos-sible explanations have been proposed to explain this apparent paradox, mainly the idea of selective mortality, which is a hypothesis that many individuals with high levels of total cholesterol might experience an earlier onset of severe coronary heart disease, leading to disproportionately greater mortality before reaching an advanced age. [76][77][78] It has also been argued that low cholesterol levels may reflect an underlying serious disease or poor nutritional status, which could predispose to a poor outcome after stroke.…”
Section: Discussionmentioning
confidence: 99%
“…3 Moreover, low TCh and triglycerides in the first hours after ICH are strong independent predictors of in-hospital mortality, 4 and surprisingly higher cholesterol levels have been associated with better short-term outcomes after acute strokes, independently of subtype, vascular territory, age, and glycemia. 5,7 Studies have reported a U-shaped relation between TCh and mortality from all causes. 8 Indeed, TCh tends to decrease among old persons, probably related to a poor health, confounding the association TCh and long-term mortality.…”
Section: Discussionmentioning
confidence: 99%